Reclaiming the Middle Path: Historical Trajectories of Moderate Islamic Education in Indonesian Pesantren of the Sixteenth Century - Mohamad Anang Firdaus; Rosyidin, Muhammad Abror; Afabih, Abdillah; Bachtiar, Hafidz Ilham (Didaktika Religia, 2025)
Pesantren have historically been recognized as key institutions in shaping moderate Islamic thought in Indonesia. However, recent shifts in certain pesantren reveal the emergence of more rigid and radical orientations, prompting the need to revisit their intellectual and theological foundations. This study investigates the genealogical roots of pesantren’s wasatiyah (moderate) orientation as it developed in the sixteenth century. Employing a qualitative method, this research is grounded in a literature-based analysis of scholarly works on Islamic education and pesantren traditions. Textual sources were selected for their relevance to the development of moderate Islamic thought in Indonesian contexts. The findings reveal three interrelated factors that underpin the emergence of moderation in pesantren: the dialectical engagement between local culture and Islam; a dialogical approach embedded in their manhaj thinking; and the theological grounding in Ahlus Sunnah wal Jama‘ah. Together, these factors form a framework that supports pesantren as enduring institutions of balanced and inclusive Islamic education. Reaffirming this genealogy is essential in addressing contemporary deviations from pesantren’s original ethos.